Removing Rubbish and Laying Foundations: Berkeley's Solution to the Sceptical Problem - WEST, PETER (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Philosophy, 2020)
In this dissertation, I argue that while Berkeley can and should be characterised as an idealist, an immaterialist, and an anti-abstractionist, he is, above all, an anti-representationalist thinker. My contention is that the arguments Berkeley puts forward in A Treatise Concerning the Principles of Human Knowledge (1710) and Three Dialogues Between Hylas and Philonous (1713) are ultimately aimed at undermining representationalism. Representationalism is an epistemological view that was widely accepted amongst Berkeley s predecessors in the seventeenth-century and entails that our knowledge of things in the world is mediated by ideas which exist only in the mind and represent them. I argue for this conclusion across six chapters which are split between three parts.
APPROVED
Keywords: Berkeley; Idealism; Immaterialism; Representation; Scepticism